CCP encyclopedia of Philippine art (Cultural Center of the Philippines Distributed Processing Systems, 1998)
This is the CD-ROM version of the 10-volume encyclopedia first published in 1994. It contains the updated biographical entries of those who received the National Artist Awards and those who passed away since 1994. All other entries follow the cut-off date of 1992 set by the first edition. It also contains videoclips of Filipino films, theater and dance, and audio samples of Philippine music and musical instruments.